2021
DOI: 10.2478/acss-2021-0002
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Turkish Sign Language Recognition Using Cascade Voting Approach with Handcrafted Features

Abstract: In this study, a machine learning-based system, which recognises the Turkish sign language person-independent in real-time, was developed. A leap motion sensor was used to obtain raw data from individuals. Then, handcraft features were extracted by using Euclidean distance on the raw data. Handcraft features include finger-to-finger, finger -to-palm, finger -to-wrist bone, palm-to-palm and wrist-to-wrist distances. LR, k-NN, RF, DNN, ANN single classifiers were trained using the handcraft features. Cascade vot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Numerous studies on variant SL, such as ASL [17][18][19][20][21][22][23][24][25], BSL [26], Arabic SL [1,27,28], Turkish SL [29,30], Persian SL [31][32][33][34], Indian SL [35,36], and others, have been carried out in recent years. To the best of our knowledge, the only accessible studies focused on KuSL and consisted of 12 classes [37], 10 classes [38], and 84 classes [39].…”
Section: Related Workmentioning
confidence: 99%
“…Numerous studies on variant SL, such as ASL [17][18][19][20][21][22][23][24][25], BSL [26], Arabic SL [1,27,28], Turkish SL [29,30], Persian SL [31][32][33][34], Indian SL [35,36], and others, have been carried out in recent years. To the best of our knowledge, the only accessible studies focused on KuSL and consisted of 12 classes [37], 10 classes [38], and 84 classes [39].…”
Section: Related Workmentioning
confidence: 99%
“…Recently, Several studies have been performed on several sign languages, including ASL [13][14] [15][16] [17] [18] [19][20], BSL [21]. Arabic sign language (ArSL) [1][22] [23], Turkish sign language [24][25],Persian sign language [26] [27] [28], Indian sign language [29] [30], and to the best of the authors' knowledge, the only three available researches have been on KuSL, including 12 classes [31], 10 classes [32], and 84 classes [33].…”
Section: Related Workmentioning
confidence: 99%
“…Modern research results make it clear that machine learning methods [8][9][10][11][12][13][14][15][16] based on deep neural networks [8][9][10][11][12][13][14][15], in comparison with traditional classical approaches [7,16,17], which are based on linear classifiers (e.g., the support vector method (SVM) or hidden Markov classification (HMC)), can demonstrate good results in segmentation, classification, and recognition as static and dynamic sign language (SL) elements. Thus, with the help of two-threaded convolutional neural networks [2,9,10], it is possible to extract the spatiotemporal features of a gesture from full-color images (RGB format) and 3D frames (depth map) of video streams separately.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, with the help of two-threaded convolutional neural networks [2,9,10], it is possible to extract the spatiotemporal features of a gesture from full-color images (RGB format) and 3D frames (depth map) of video streams separately. In turn, a deep neural network (DNN) is used to perform segmentation and classification of the hand shape with multiple architectures and sizes of the input images [4,11]. In addition, it was revealed that the architecture of the long short-term memory (LSTM) neural networks [1,3,12,13,15,[18][19][20], with the help of long and short-term memory, can extract the spatiotemporal characteristics of a gesture from sequences of previously annotated 2D regions with a gesture.…”
Section: Introductionmentioning
confidence: 99%